PENGGUNAAN METODE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) DALAM PEMBELAJARAN MENULIS TEKS ANEKDOT - Ratnasari, Yanti; Aripin, Aripin; Suhara, Alfa Mitri (IKIP Siliwangi, 2019)
This research was motivated by the difficulties experienced by students in writing, including writing anecdotal texts. Students still find it difficult to develop ideas and ideas to create humor in the text. The problem in this study is how to use the STAD method for learning to write an anecdotal text? Is there a difference in the ability to write anecdotal text before and after using the STAD method? This study was held to determine the use of the STAD method in learning to write anecdotal texts. Knowing the results of student writing for learning to write anecdotal texts that apply the STAD method. The use of research design is one group pretest-posttest. The sample that the author examined was class X with a total of 25 students. Data collection techniques used in this study were in the form of tests either at the beginning (pretest) or at the end (posttest). According to the data presented, the average results obtained before using the learning method amounted to 43.96 and after using the method, the final average score (posttest) was obtained at 67.44. The result of anecdotal text writing ability increased to 23.48 points. Based on the results of the normality test of 0.200> 0.05 stated normal distribution, the results of the homogeneity test of 0.48> 0.05 have a homogeneous variance, and the results of the t-test sig (2-tailed) of 0,000 <0,05 stated that the hypothesis is accepted.